The impact of regional integration: assessing opportunities and challenges for ASEAN’s transitional economies - Rini Suryati Sulong; Lim, Beatrice, Fui Yee (Penerbit UMS, 2015)
The growing economic and political interdependencies of markets around the world characterize the complexity of globalization in the 21st century. For most developing countries, globalization of markets presents a greater opportunity to attract foreign investments that would help stimulate national economic growth. Among the factors that influence a company’s decision to invest in a foreign location, accessibility to markets and stability of the host countries’ political environment are important determinants because internal political stability is interdependent with internal economic stability. We propose that the determinants of investments in the transitional economies of ASEAN are not confined to its national political stability alone but rather to regional political stability and the opportunity of greater market share acquiesced by regional economic integration. This paper therefore aims to stimulate discussions regarding the influence of regional integration on national development, as well as to contribute to the greater body of knowledge of regional integration studies.